Geotechnologies: discussion and analyses about evolution of Global Navigation Satellite System -GNSS - Prina, Bruno Zucuni; Trentin, Romario (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper has the aim of to perform one theoretical review about the concept and applications the “geotechnologies” with a focus main to Global Navigation Satellite System. This study aimed to in build an full bibliographic content researching information about the evolution of geo-technologies. Thus, the justification this research is to generate a broad and complete material to identify the evolution of geotechnologies (with emphasis on satellite positioning) as well as identify the main applications and contributions this theme to society. From the methodological stages implemented in this paper, are defined distinct views about the subject, may characterize the historical evolution of geotechnologies, as well as its main practical applications. Thus, was concluded the geotechnologies are fully rising and, that GNSS is amazingly rich area of applications, which corroborate with humans with the development of various sectors of society.